The includers the 7 traits of culturally savvy, anti-racist leaders - Phillips, Collette A. M. (Ascent Audio, 2024)
"It's a simple fact that the people who make policy and oversee government, sports, business, and the arts and entertainment are most commonly white men. Another fact: We cannot achieve meaningful progress if we exclude the very people who have the power to make systemic change. This handbook is free of any attempts to shame, blame, or guilt leaders for the choices they made in the past or privileges they were born with. Instead, listeners will learn to view the work they do through a racial equity lens so they can easily and immediately begin making changes. In The Includers, Colette Phillips explores the core qualities that inclusive leaders share: character, cultural intelligence, connections, communications, collaboration, courage, and commitment. With humor and poignancy, and backed by research, Phillips shares stories of real Includers: the CEOs, politicians, and public figures-all white male allies-she's admired, known, and, in some cases, counseled. For leaders who are ready to do their part, this eye-opening guide offers practical, actionable insights from allies and advocates who are willing to listen, learn, and ""lead from behind"" to create sustainable systemic change.".
Online resource; title from title details screen (O'Reilly, viewed February 19, 2024)
Keywords: Leadership -- Moral and ethical aspects; Anti-racism; Organizational change; Social change; Leadership; Aspect moral; Antiracisme; Changement organisationnel; Audiobooks; Livres audio